Effects of Limiting Nitrate Concentration on Morphological and Differential Expression of High- and Low-Affinity Nitrate Transporter Genes of Diverse Wheat Genotypes - Kumar, Amresh; Arya, Aditi; Sinha, Subodh Kumar (International Journal of Ecology and Environmental Sciences, 2024)
Nitrate uptake in wheat is an essential and complex process that involves multiple proteins. Roots are the major plant organs that take nitrate molecules from the soil and transport them to the above-ground parts. They involve several high- and low-affinity nitrate transporters located in the plasma membrane of different root and shoot tissues. In the present study, we investigated the responses of different selected wheat genotypes, released in India for different agroclimatic regions in a different year, for their biomass, root traits, and expression of high- and low-affinity nitrate transporters genes under optimal and limiting nitrate conditions at the 14 days seedling stage. The maximum number of genotypes showed increased biomass and total root size (TRS) under nitrate starvation, which indicates that the variation of TRS traits in different genotypes responds differently to nitrate starvation. Gene expression of TaNRT2.1-4 showed up-regulated expression under low external N-concentration in all genotypes. Among the four TaNRT1.1 orthologs, TaNPF6.1 and TaNPF6.4 showed up-regulated expression, whereas TaNPF6.2 and TaNPF6.3 expressed down-regulated in root at higher nitrate concentrations. TaNRT1.1 (TaNPF7.1 and TaNPF7.2) showed up-regulated in root at optimum nitrate concentrations. TaNPF6.1, TaNPF6.4, TaNPF7.1, and TaNPF7.2 showed a typical expression of low-affinity nitrate transporter genes under optimum external N-concentrations. Our findings indicate that HD2967, NP890, and VL804 showed the highest expression of TaNRT2.1-4, TaNRT1.1, and TaNRT1.5, respectively, possibly involved in nitrate uptake and translocation (from root to shoot).